PEMBINAAN KELOMPOK SADAR WISATA DI DESA NONONGAN - Liliana Dewi; Yasmin Nur Sya’Ban (JURNAL PENGABDIAN MANDIRI, 2022)
The objective is to guidance Kelompok Sadar Wisata di desa Lembang Nonongan, then determine the obstacles and positive impacts of this coaching activity. The location of this qualitative research is in Lembang Nonongan Village, North Toraja Regency. This research took five resource persons involved in the coaching activities: the interview, observation, and documentation techniques—the training for the community through socialization about Sadar Wisata and the importance of Kelompok Sadar Wisata. The results of the interviews were then analyzed using a SWOT analysis. The results are training about development homestay, a healthy cook culinary, promotion, implementation of Sapta Pesona, and CHSE.. In this coaching activity, there are still some obstacles in developing human resources in the Nonongan Tourism Village.